This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
With y = 4 − x , the second equation becomes
x ( 4 − x ) + 6 z = z 2 + 1 3 ⟹ z 2 − 6 z + ( 1 3 + x 2 − 4 x ) = 0 .
Using the quadratic equation, we see that the possible values for z are
z = 2 6 ± 3 6 − 4 ( 1 3 + x 2 − 4 x ) = 2 6 ± − 1 6 − 4 x 2 + 1 6 x =
3 ± − ( x 2 − 4 x + 4 ) = 3 ± − ( x − 2 ) 2 .
Since − ( x − 2 ) 2 ≤ 0 for real x , for z to also be real we will require that x = 2 , in which case z = 3 and y = 4 − x = 2 .
Thus x + y + z = 2 + 2 + 3 = 7 is the unique solution over R .